Clinical Predictors of Acute Brain Injury in Carbon Monoxide Poisoning Patients With Altered Mental Status at Admission to Emergency Department. (31st July 2018) - Kim, Youn‐Jung; Sohn, Chang Hwan; Seo, Dong Woo; Oh, Bum Jin; Lim, Kyoung Soo; Kim, Won Young
Abstract: Objectives: Objective screening tool for patients at a high risk of developing acute brain injury (ABI) is necessary for the proper treatment of carbon monoxide (CO) poisoning patients. The aim of this study is to identify clinical factors that could predict ABI due to CO poisoning in patients with an altered mental status. Methods: A prospectively collected CO poisoning registry at a single academic medical center was retrospectively analyzed. CO poisoning patients with an altered mental status at the emergency department, defined as unalert on the alert/responsive to voice/responsive to pain/unresponsive scale and underwent diffusion‐weighted magnetic resonance imaging (DW‐MRI) between January 1, 2013, and December 31, 2015, were included. ABI was defined as the presence of acute hypoxic brain lesions. Clinical predictors of ABI were identified by multivariate logistic regression analysis. Results: Of 180 patients, 67 (37.2%) had ABI as revealed by DW‐MRI. Multivariate analysis showed that CO exposure duration > 5 hours (adjusted odds ratio [AOR] = 7.082; 95% confidence interval [CI] = 3.463–15.014; p < 0.001) defined as the time between CO exposure and rescue, abnormal white blood cell count (AOR = 2.568, 95% CI = 1.188–5.700, p = 0.02), and abnormal creatinine concentration (AOR = 2.667, 95% CI = 1.110–6.605, p = 0.03) were predictors of ABI. CO exposure duration had the highest predictive value (area under the curve, 0.815), and the optimal cutoff value was 5 hours. Moreover, increasing exposure durations (quartile) indicated a stepwise increase in the risk of ABI. Conclusions: In CO poisoning patients with an altered mental status, CO exposure duration was useful for predicting ABI, which may help clinicians or paramedics identify high‐risk patients and provide treatment on priority.